2021
DOI: 10.2176/nmc.oa.2020-0412
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility of Mechanical Thrombectomy for Acute Ischemic Stroke Patients Aged 90 Years or Older Compared to Younger Patients

Abstract: Mechanical thrombectomy (MT) is a proven treatment for acute ischemic stroke (AIS). However, the efficacy of this treatment is uncertain for very elderly patients. This study aimed to investigate the safety and effectiveness of MT in 90 years or older patients compared with younger patients. We retrospectively reviewed AIS patients treated with MT between October 2018 and June 2020 in our institution. Patients were divided into two groups: aged ≥90 and <90 years. We compared the following factors: functional o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 27 publications
0
3
0
Order By: Relevance
“…Ischemic stroke represents a major health concern worldwide. Importantly, due to shifting living and dietary habits, the average age of occurrence of stroke has gradually become younger [ 44 , 45 ]. In terms of the treatment of stroke, intravenous thrombolysis is the most commonly used method, although the effective time window is limited [ 3 ].…”
Section: Discussionmentioning
confidence: 99%
“…Ischemic stroke represents a major health concern worldwide. Importantly, due to shifting living and dietary habits, the average age of occurrence of stroke has gradually become younger [ 44 , 45 ]. In terms of the treatment of stroke, intravenous thrombolysis is the most commonly used method, although the effective time window is limited [ 3 ].…”
Section: Discussionmentioning
confidence: 99%
“…11 On the contrary, several studies reported good outcomes in older adult patients after strict screening. 12 Outcomes of EVT among older adults are better than among the older adults received general supportive measures. The lower NIHSS score at the admission, shorter duration of EVT, and better thrombolysis in cerebral infarction (TICI) score could be the predictors of good outcome.…”
Section: Introductionmentioning
confidence: 99%
“…As age is a major risk factor of stroke, and more than 80% of strokes occurring in elderly patients over the age of 65 (9). However, the elderly with AIS were usually excluded from large randomized controlled stroke clinical trials because of their high risk of complication, poor prognosis (7,10), although mechanical thrombectomy (MT) is still recommended as preferred treatment for elderly patients (11).…”
mentioning
confidence: 99%